2019
DOI: 10.1016/j.neuroimage.2018.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Screen media activity and brain structure in youth: Evidence for diverse structural correlation networks from the ABCD study

Abstract: The adolescent brain undergoes profound structural changes which is influenced by many factors. Screen media activity (SMA; e.g., watching television or videos, playing video games, or using social media) is a common recreational activity in children and adolescents; however, its effect on brain structure is not well understood. A multivariate approach with the first cross-sectional data release from the Adolescent Brain Cognitive Development (ABCD) study was used to test the maturational coupling hypothesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
96
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(121 citation statements)
references
References 69 publications
10
96
2
3
Order By: Relevance
“…To indicate screen use, participants simply pick from a list of five standard time ranges, giving separate answers for each media category and for weekdays and weekends. (The first report about media use from this study, published last year, showed a small or no relationship between media exposure and brain characteristics or cognitive performance in computer-based tasks 9 . )…”
Section: Thomas Peter/reutersmentioning
confidence: 61%
“…To indicate screen use, participants simply pick from a list of five standard time ranges, giving separate answers for each media category and for weekdays and weekends. (The first report about media use from this study, published last year, showed a small or no relationship between media exposure and brain characteristics or cognitive performance in computer-based tasks 9 . )…”
Section: Thomas Peter/reutersmentioning
confidence: 61%
“…[12][13][14] The World Health Organization recently released even more restrictive recommendations for children younger than 5 years, discouraging screen time and advocating greater study of its implications for health and development. 15 Recent evidence suggests that screen-based media use poses neurobiological risks in children, [16][17][18][19] yet its associations with early brain development are largely unknown, particularly during the dynamic span of development before kindergarten. 10 Although sensory networks mature relatively early, 11 those sensory networks for higher-order skills, such as language, 12 executive function, 20,21 multimodal association, 13 and reading, 22,23 exhibit protracted development 11,14 and are dependent on constructive stimulation in the home.…”
mentioning
confidence: 99%
“…A linear mixed-effect model (LMM) was used to test the associations of the exposure to NVP with the brain morphometric measures and with the children's cognitive scores from the NIH Cognitive Toolbox and the psychiatric problems scores from the Child Behavior Checklist noted above that are provided by ABCD. As recommended by the ABCD and used in many studies [40,41], a linear mixed-effects model (LMM) was used to model the correlated observations within families due to twins and siblings and at sites. In this way, the LMM was specified to model family nested within the site.…”
Section: Statistical Analysis Association Analysismentioning
confidence: 99%